An evaluation of preferences on electronic and print formats of publication of various types of clienteles of three law school libraries - Garcia, Domingo A. III (2002)
The study aimed at ascertaining the format preferences of law library clientele with regards to their information needs. The study also looked into the attitudes of the law library clientele regarding the aforementioned publication formats. In order to determine this, a structured questionnaire was sampled to sample population determined using the Stratified Random sampling method. Of the 187 samples users 187 questionnaires were returned. The respondents' answers were then tabulated, and results analyzed.